2012
DOI: 10.1074/mcp.m111.014209
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteome Dynamics: Analysis of Lipoproteins and Acute Phase Response Proteins with 2H2O Metabolic Labeling

Abstract: Understanding the pathologies related to the regulation of protein metabolism requires methods for studying the kinetics of individual proteins. We developed a 2 H 2 O metabolic labeling technique and software for protein kinetic studies in free living organisms. This approach for proteome dynamic studies requires the measurement of total body water enrichments by GC-MS, isotopic distribution of the tryptic peptide by LC-MS/MS, and estimation of the asymptotical number of deuterium incorporated into a peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 52 publications
1
63
0
Order By: Relevance
“…In animal models, body 2 H 2 O enrichments can be 3.0-8.0% Klionsky et al, 2012;Li et al, 2012;Price, Holmes, et al, 2012;Price, Khambatta, et al, 2012). Examples of body water labeling protocols in humans are described in Fig.…”
Section: Constraints On 2 H 2 O Administration and Factors To Considementioning
confidence: 98%
See 4 more Smart Citations
“…In animal models, body 2 H 2 O enrichments can be 3.0-8.0% Klionsky et al, 2012;Li et al, 2012;Price, Holmes, et al, 2012;Price, Khambatta, et al, 2012). Examples of body water labeling protocols in humans are described in Fig.…”
Section: Constraints On 2 H 2 O Administration and Factors To Considementioning
confidence: 98%
“…There are potential applications of isotope analyses of daughter ions, such as immonium ions from amino acids, in MS/MS mode using ion traps (T. Angel, unpublished observations). We have found that TOF instruments operated in MS-only mode provide sufficient isotope accuracy and precision required to detect subtle changes in peptide isotopomer distributions achieved through body water enrichments of 1-5% Decaris et al, 2014;Klionsky et al, 2012;Li et al, 2012;Price, Holmes, et al, 2012;Price, Khambatta, et al, 2012).…”
Section: Ms Instrumentationmentioning
confidence: 98%
See 3 more Smart Citations